FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN POLA MAKAN MAHASISWA PADA MASA PANDEMI COVID-19 DI KOTA KUPANG - Asweros Umbu Zogara; Astuti Nur (CHMK HEALTH JOURNAL, 2022)
In today's world, COVID-19 has become a pandemic. It spreads swiftly and kills a lot of people. The COVID-19 epidemic has resulted in numerous societal changes. The community must develop health procedures and improve healthy habits as a result of the changes. A nutritious diet at all levels of society, including students, is one of the healthy lifestyles that must be followed by the community. The A cross-sectional design was adopted in this investigation. The study took place at the Health Poltekkes, Ministry of Health, Kupang, from June to December 2020. The research sample consisted of 204 students who were chosen using a simple random sampling. The role of parents (p value = 0.00) and student nutritional behavior (p value = 0.00) are factors connected to student eating patterns, according to the findings of this study. Not connected to the student's diet include father's education (p value = 0.88), mother's education (p value = 0.72), father's occupation (p value = 0.64), mother's occupation (p value = 0.91), and nutrition knowledge (p value = 0.20). During the COVID-19 epidemic, diet plays a crucial role in developing students immunity. As a result, it is vital to provide ongoing education so that students can adopt healthy eating pattern. Keyword: students, eating pattern, COVID-19